Strategy for Developing Four-Wheel Tractor Utilization at the Agricultural Agribusiness UPTD of Maros Regency - Kartini Kartini; Iqbal; Olly Sanny Hutabarat; Diyah Yumeina (Salaga Journal, 2026)
Agricultural mechanization through four-wheel tractors (TR4) plays a critical role in improving rice farming efficiency and addressing persistent labor shortages in rural areas. However, research on the institutional development strategies of government-managed Alsintan service units (UPTD) at the district level remains limited in the Indonesian context. This study aims to (1) identify internal and external factors influencing TR4 utilization at the UPTD of Agricultural Agribusiness Management of Maros Regency, and (2) formulate strategic development recommendations. Data were collected through structured interviews and questionnaires involving 15 purposively selected respondents comprising UPTD managers, field extension officers, farmers, and representatives from related agencies. SWOT analysis was applied using Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices with weighted scoring. Results indicated that the IFAS strength score (3.340) exceeded the weakness score (3.098), and the EFAS opportunity score (3.091) exceeded the threat score (2.856), positioning the UPTD in Quadrant I (Aggressive/SO Strategy). The identified priority strategies are: (1) socialization of TR4 services supported by relevant government agencies; (2) strengthening multi-stakeholder cooperation; (3) application of competitive rental rates; and (4) expansion of TR4 fleet availability through policy advocacy. These findings provide evidence-based recommendations for institutional development and agricultural mechanization policy in Maros Regency.